Influence of pulsating flow frequencies towards the flow angle distributions of an automotive turbocharger mixed-flow turbine. (1st July 2015) - Padzillah, M.H.; Rajoo, S.; Yang, M.; Martinez-Botas, R.F.
Highlights: Flow angle behaviour at vane inlet is similar for both steady and unsteady operations. Guide vanes enhance fluctuation range of flow angle by 300% for unsteady conditions. Flow angle at the turbine inlet is more stable during pressure decrement period. Adjustment to the pressure drop in the volute section is recommended. Abstract: This paper aims to provide a detailed understanding of the flow interaction within the complex geometry of turbine stage coupled with reflection and superposition of the imposed unsteady pressure waves. The defining performance characteristic of a turbomachines is the inlet flow angle at its leading edge, which in most cases limit its optimum operational range. Pulsating flow field, typical to turbocharger turbine due to opening and closing of the exhaust valves, further deteriorates the flow angle distribution around its circumference, hence performance. To investigate this phenomena and how it differs from the steady state equivalent, a fully validated 'cold flow' Computational Fluid Dynamics (CFD) analysis was carried out. For this purpose, 4 unsteady CFD simulations of 20 Hz, 40 Hz, 60 Hz and 80 Hz together with the steady state simulations have been conducted at 30, 000 rpm turbine speed. Discussions in this paper aim to provide a better insight on the flow angle behaviour in pulsating flow field. Evidences are shown where flow angle swings over a wide range (300% more than the steady state condition) in pulsating flow field as it propagates through the guide vanes. It was also found that the flow angle fluctuations during pressure drop period is significantly lower as compared to that during pressure increment period by ( 19 ° ). This work also leads to a recommendation of correction factor in applying quasi-steady assumption of the rotor wheel. Without this correction, the prediction results could lead to underestimation of mass flow parameter up to 8% at high pressure ratio.